Evolving ischemic stroke subtypes in 15 years: A hospital-based observational study. Issue 4 (April 2022) - Ip, Bonaventure; Au, Lisa; Chan, Anne; Fan, Florence; Ip, Vincent; Ma, Sze H; Ma, Karen; Mok, Vincent; Lau, Alexander; Leng, Xinyi; Leung, Howan; Wong, Adrian; et al.
Background: Depicting the time trends of ischemic stroke subtypes may inform healthcare resource allocation on etiology-based stroke prevention and treatment. Aim: To reveal the evolving ischemic stroke subtypes from 2004 to 2018. Methods: We determined the stroke etiologies of consecutive first-ever transient ischemic attack or ischemic stroke patients admitted to a regional hospital in Hong Kong from 2004 to 2018. We analyzed the age-standardized incidences and the two-year recurrence rate of major ischemic stroke subtypes. Results: Among 6940 patients admitted from 2004 to 2018, age-standardized incidence of ischemic stroke declined from 187.0 to 127.4 per 100, 000 population (p < 0.001), driven by the decrease in large artery disease (43.0–9.67 per 100, 000 population (p < 0.001)), and small vessel disease (71.9–45.7 per 100, 000 population (p < 0.001)). Age-standardized incidence of cardioembolic stroke did not change significantly (p = 0.2). Proportion of cardioembolic stroke increased from 20.4% in 2004–2006 to 29.3% in 2016–2018 (p < 0.001). Two-year recurrence rate of intracranial atherothrombotic stroke reduced from 19.3% to 5.1% (p < 0.001) with increased prescriptions of statin (p < 0.001) and dual antiplatelet therapy (p < 0.001). In parallel with increased anticoagulation use across the study period (p < 0.001), the two-year recurrence of AF-related stroke reduced from 18.9% to 6% (p < 0.001). Conclusion: Etiology-based risk factor control might have led to the diminishing stroke incidences related to atherosclerosis. To tackle the surge of AF-related strokes, arrhythmia screening, anticoagulation usage, and mechanical thrombectomy service should be reinforced. Comparable preventive strategies might alleviate the enormous stroke burden in mainland China.